Meningkatkan hasil belajar IPA menggunakan audio pop up book materi metamorfosis SDN 3 blimbing - Fildza Hani Fati Abidah; Nataria Wahyuning Subayani; Ismail Marzuki (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2024)
To support the smooth learning process in the classroom, learning media is very necessary. In teaching and learning the role of learning media is also important to help the learning process. So this research aims to improve student learning outcomes in science subjects using pop up book audio media. The type of research used is Classroom Action Research (PTK) through four stages, namely planning, implementation, observation and reflection at SDN 3 Blimbing. The instruments used in this research were teacher observation sheets, student observation sheets, documentation and learning results test sheets. The results of this research show that those who use audio pop up books have a metamorphosis in science learning. Student learning outcomes have increased from the 2 learning cycles carried out, which can be seen from the student learning outcomes where in the first cycle, student completion was 43%, which shows that students can understand metamorphosis material but cannot differentiate between lava and pupae, tadpoles and tailed frogs, pupae and larvae. larva, nymph and imago. Meanwhile, in cycle II, learning outcomes increased by 52.4% to 95.4% .  This indicates that the use of audio pop up book media on metamorphosis material can improve learning outcomes significantly. Therefore, it is recommended that science learning in elementary schools use more real learning media.